Asset overhang and the green transition - Hans Degryse; Tarik Roukny; Joris Tielens (EconPol Forum, 2023)
Environmental technologies threaten dirty legacy portfolios of external financiers. "Asset overhang" refers to an investor's incentive not to finance disruptive green firms in an attempt to protect exposed legacy positions. Empirically, asset overhang renders green disruptors up to 4.4 percentage points less likely to receive external finance. The presence of financiers with low asset overhang trigger systemwide incentives to fund green firms. Limited policy interventions aimed at reducing such overhang can alleviate financial barriers to the green transition
Keywords: 330